Navigating Housing Instability and Substance Use: Hidden Tensions Facing Youth in Small Town America. Issue 46 (3rd May 2020) - Curry, Susanna R.; Samuels, Gina Miranda; Cerven, Christine; Dworsky, Amy
Abstract: Recent scholarship indicates that youth homelessness is a significant problem outside urban areas. However, previous studies have not examined how local contexts shape the experiences of youth who are homeless in rural areas and small towns with high rates of poverty and epidemic drug use. To address this gap, this analysis draws from two components of a large national study of homelessness among youth, using data collected in a small non-urban setting in the Northwest including (1) a subset of 41 (out of 215 nationally) in-depth interviews with youth and (2) a subset of 16 surveys (out of 523 nationally) with service providers. We explored availability of services and how youth navigate housing instability and the service landscape in small communities. We discovered that current or prior addictions sometimes posed risks to the safety of youth and compromised their ability to rely on family supports – a support proving critical in the absence of a formal service infrastructure. Our results suggest that youth experiencing housing instability in the context of high rates of drug use and limited formal services must often choose between meeting competing needs: a place to stay versus sobriety. We discuss the implications for policy, practice, and research.